(untitled) (International Journal of Language, Literacy and Translation, 2024)
Culture is embedded in and reflected by language. Malaysian Standard English encompasses a vast number of indigenised words borrowed from Malay, Chinese, and Indian cultures (Baskaran, 2005). Malaysian Indians, the third-largest ethnic group in Malaysian society, have played a significant role in shaping Malaysian Standard English (MSE) through lexical borrowing from their rich and diverse cultural heritage. This study investigates the influence of Malaysian Indian culture on lexical borrowing in MSE. A survey adapted from Tan (2009a, 2009b) comprising both qualitative and quantitative questions was administered to 60 Malaysian Indian students at one of the public universities in Malaysia. It gathers 134 MSE words borrowed from Indian culture and examines the motivations for borrowing Malaysian Standard English words from Indian culture. The borrowed words are categorised under different cultural items like festivals, martial arts and acrobatics dances, medicine, food, social and recreational activities, religion, and clothing and apparel. The need to emphasise one’s Indian ethnic background emerged as the key motivation behind the adoption of the words in MSE. Also, the least significant motivation is the need to fill the lexical gap, which is different from many previous studies. By collecting those borrowed words and their underpinning motivations, this study offers valuable insights into the obvious relationship between language and culture, shedding light on how Malaysian Standard English reflects the influence of Malaysia’s Indian community. It also provides opportunities for people to acquire familiarity with Indian culture and promote smooth cross-cultural communication among Malaysian Indian ethnicity and other ethnic groups in Malaysia.